2021
DOI: 10.1111/sms.14026
|View full text |Cite
|
Sign up to set email alerts
|

Meeting physical activity and screen time among Colombian adolescents with or without sensory‐related problems

Abstract: The aim of this study was to assess the extent to which adolescents with and without visual and hearing‐related problems meet physical activity (PA) and recreational screen time (ST) recommendations in a representative Colombian sample. A total of 35,404 adolescents aged 13–17 years were included from the Encuesta Nacional de Salud Escolar (ENSE) (Colombia). Sociodemographic‐related information, anthropometric variables, PA, ST, and both visual‐ and hearing‐related problems were collected by self‐administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Regrettably, a very low proportion of participants in this study reported concurrent achievement of PA and ST recommendations, with very low rates in the pre-pandemic, during restrictions and in the restriction-easing phase, respectively, of 21.1%, 5.3% and 10.5%. Accordingly, a recent investigation on the prevalence of Colombian adolescents meeting PA and ST guidelines showed similar rates (7.8%), hampered by the presence of sensory problems (Lopez-Gil et al 2021). The disability itself is a key barrier to PA participation and ST recommended dose.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regrettably, a very low proportion of participants in this study reported concurrent achievement of PA and ST recommendations, with very low rates in the pre-pandemic, during restrictions and in the restriction-easing phase, respectively, of 21.1%, 5.3% and 10.5%. Accordingly, a recent investigation on the prevalence of Colombian adolescents meeting PA and ST guidelines showed similar rates (7.8%), hampered by the presence of sensory problems (Lopez-Gil et al 2021). The disability itself is a key barrier to PA participation and ST recommended dose.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, a recent investigation on the prevalence of Colombian adolescents meeting PA and ST guidelines showed similar rates (7.8%), hampered by the presence of sensory problems (Lopez‐Gil et al . 2021 ). The disability itself is a key barrier to PA participation and ST recommended dose.…”
Section: Discussionmentioning
confidence: 99%